Sexual Function of Patients With Endometrial Cancer Enrolled in the Gynecologic Oncology Group LAP2 Study. Issue 9 (1st November 2012) - Carter, Jeanne; Huang, Helen; Chase, Dana M.; Walker, Joan L.; Cella, David; Wenzel, Lari
Abstract : Objectives: To present responses to sexual function items contained within the quality of life (QOL) survey of the Gynecologic Oncology Group LAP2 study, to investigate associations between sexual function and other factors (such as relationship quality and body image), and to explore patterns of response in patients with endometrial cancer. Methods: Participants enrolled in the LAP2 QOL study arm completed a self-report QOL survey, which contained sexual function items, before surgery, and at 1, 3, and 6 weeks and 6 months after surgery. Responses to sexual function questions were classified into 3 patterns—responder, intermittent responder, and nonresponder—based on whether the sexual function items were answered when the QOL survey was completed. Results: Of 752 patients who completed the QOL survey, 225 completed the sexual function items within the QOL survey, 224 responded intermittently, and 303 did not respond at all. No significant differences of sexual function were found between the patients randomized to laparoscopy compared to laparotomy. Among those who responded completely or intermittently, sexual function scores declined after surgery and recovered to presurgery levels at 6 months. Sexual function was positively associated with better quality of relationship ( P < 0.001), body image ( P < 0.001), and QOL ( P < 0.001), and negatively associated with fear of sex ( P < 0.001). Conclusion: Our findings suggest that younger patients, those who were married, and those who had quality relationships were more likely to answer the sexual function items and have better quality of sexual function. Factors such as age, relationship quality, body image, and pain may place women with endometrial cancer at risk for sexual difficulties in the immediate recovery period; however, sexual function improved by 6 months postoperatively in our cohort of patients with early-stage endometrial cancer.